Exploring Job Satisfaction: A Comparative Study of Nurses and Healthcare Administrative Professionals Across Hierarchical Levels - Nath, Micah (Digital Repository of Theses, 2024)
Background As much as researchers remain intrigued by the dilemma job satisfaction presents, it is a major concern for employers as well as employees. It is especially a debatable topic in a healthcare organisation, where under one roof, different job profiles operate. Through this thesis, a parallel was drawn between various factors affecting job satisfaction among multi-disciplinary employees of a healthcare organisation, specifically nurses and the administrative personnel. While analysing how an employee perceives job satisfaction, depending upon the individual factors, this study determined the role of transformative leadership in enhancing job satisfaction. Methods The study used both quantitative and qualitative methods to draw a parallel between the factors affecting different classes of healthcare employees at various hierarchical levels. A survey analysis was done through a defined set of questionnaires. The target population was multidisciplinary healthcare workers, nurses, and administrative healthcare personnel. Results The data was analysed using content and construct validity, and the correlation method was used to establish the credibility of the study. Discussion and Conclusion The study’s findings could be valuable to healthcare setups as they might fill a gap in understanding strategies to increase job satisfaction among multi-disciplinary professionals. This research can contribute to leadership growth, leadership development theory, job satisfaction strategies, and healthcare setup performance. Furthermore, it will help provide in-depth insights into how different classes of healthcare employees perceive job satisfaction among themselves. The study will establish the various factors that impact job satisfaction among the same class of healthcare employees at different hierarchical levels.